Late-onset capsular bag distension syndrome 33 years after cataract surgery - Rosario Alfio Umberto Lizzio; Francesco Polimeni; Andrea Dellavalle; Fabrizio D'Ancona; Martina Colombo; Stefano Mattioli; Paolo Nucci (American Journal of Ophthalmology Case Reports)
Purpose: Describe the clinical features and management of this uncommon case of late-onset Capsular bag distension syndrome that occurred 33 years after cataract surgery. Observation: An 87-year-old male was referred to our clinic complaining of blurred and gradual, painless reduction in vision in his left eye over the past year. A complete ophthalmological examination, Ultrasound biomicroscopy (UBM), anterior segment optical coherence tomography (AS-OCT), and optical biometry were performed to confirm the diagnosis. A 25-gauge pars plana vitrectomy combined with posterior capsulotomy was performed. The aspirated fluid was sent for microbiological analyses. After surgery, the patient's visual acuity returned to previous values, and anterior chamber depth slightly deepened. Samples taken were negative for bacteria. Conclusions and Importance: Late-onset Capsular bag distension syndrome may occur up to 33 years following cataract surgery. A surgical approach offers the advantage of complete clearance of the turbid fluid, also removing the residual cortical material and enabling microbial and pathological testing.